Know Your Onions : Graphic design : how to think like a creative, act like a businessman and design like a god - De Soto, Drew (2011)
Practical and immediate, without being condescending or overly technical, this book acts as a graphic design mentor who will help you come up with ideas, develop your concepts, and implement them in a way that is engaging and humorous. It gives readers the experience and ability that normally comes from years of on-the-job training. All of the essential techniques of graphic design and its digital implementation are covered. Read this book and gain 25 years of experience in how to think like a creative, act like a businessman and design like a god.
Cover title.
Keywords: Graphic arts; Graphic design (Typography); Art and Design